Learning, Inside and Out: Prior Linguistic Knowledge and Learning Environment Impact Word Learning in Bilingual Individuals. Issue 4 (2nd May 2022) - Palma, Pauline; Marin, Marie‐France; Onishi, Kristine H.; Titone, Debra
Abstract: Although several studies have focused on novel word learning and lexicalization in (presumably) monolingual speakers, less is known about how bilinguals add novel words to their mental lexicon. In this study we trained 33 English–French bilinguals on novel word‐forms that were neighbors to English words with no existing neighbors. The number of novel neighbors to each English word varied, as did the cross‐linguistic orthographic overlap between the English word and its French translation. We assessed episodic memory and lexicalization of the novel words before and after a consolidation period. Cross‐linguistic similarity enhanced episodic memory of novel neighbors only when neighborhood density among the novel neighbors was low. We also found evidence that novel neighbors of English words with high cross‐linguistic similarity became lexicalized after a consolidation period. Overall, the results suggest that similarity to preexisting lexical representations crucially impacted lexicalization of novel words by bilingual individuals. Abstract :